Agresividad en escolares y su relación con la crianza parental. Pacasmayo - 2017 - Yengle Polo, Jussara Evelyn (2018)
The present investigation is quantitative -descriptive; It was carried out in an Educational Institution of Pacasmayo District, Pacasmayo Province, from November 2017 to January 2018, in order to determine the relationship between aggressiveness in schoolchildren and parenting of mothers, fathers or guardians. The sample consisted of 100 schoolchildren and 100 mothers, parents or guardians. For data collection, a test of aggression in schoolchildren and a questionnaire for caregivers on parental parenting in their children, developed by Yengle and Goicochea (2017) was used. The results are presented in simple tables and double entry, the information was processed and analyzed by the statistical test "Chi Square". After the analysis, the following conclusions were reached: Of the total of children, 95 percent presented being non-aggressive and 5 percent aggressive. Of the total of parents 80 percent presented democratic style, 19 percent permissive style and 1 percent authoritarian style. There is statistically highly significant relationship between both variables (P = 0.000).